Waste cooking oil pretreatment using microwave and ultrasound methods - Kerras, Halima; Outili, Nawel; Meniai, Abdeslam-Hassen (Comptes Rendus. Chimie)
The present study focused on the comparison of two intensified pretreatment techniques for waste cooking oil (WCO) collected from university restaurants. The cooking oil was 100% soybean and had an acidity value (AV) of 4.48 mg KOH/g oil. Ultrasound (US) and microwave (MW) irradiations were applied as non-chemical pretreatment methods with zero generated waste. The considered factors for the MW pretreatment were power and time ranging from 100 to 800 W and from 20 to 120 s, respectively. The US pretreatment was carried out at a temperature ranging from 20 to 40 °C for a residence time ranging from 5 to 50 min. For the two non-chemical pretreatment methods, optimal conditions were as follows: for microwave irradiation, a power of 100 W, a residence time of 50 s, and an acid value reduced to 1.056 mg KOH/g; whereas, the US pretreatment reduced the AV to 1.014 mg KOH/g at 40 °C, 30 min and 100 W. Finally, the pretreated WCO under optimal conditions was used for biodiesel production using conventional transesterification. Results showed that the pretreatment methods led to good results where the best biodiesel yield was 98%, obtained with US pretreatment, while MW led to a yield of 96%. Both yields were higher than 94%, obtained for biodiesel production without any pretreatment.